2021
DOI: 10.1001/jamanetworkopen.2021.0169
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Cognitive Decline Among US Adults

Abstract: Key Points Question Does the risk of cognitive decline among US adults vary by sex? Findings In this cohort study using pooled data from 26 088 participants, women, compared with men, had higher baseline performance in global cognition, executive function, and memory. Women, compared with men, had significantly faster declines in global cognition and executive function, but not memory. Meaning These findings suggest that women ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
193
4
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 250 publications
(221 citation statements)
references
References 67 publications
21
193
4
3
Order By: Relevance
“…For example, 14/17 old females exhibited VHIPP IL-6 levels that exceeded the mean value measured in old males. These data are in line with other studies indicating that neuroinflammation accumulates in the aged female hippocampus to a greater extent than males [ 57 ] and highlights a potential mechanism whereby females display faster age-related cognitive decline than men [ 81 ] and higher rates of Alzheimer’s disease [ 82 ]. It will be of interest to future studies to understand the basis for these augmented female responses.…”
Section: Discussionsupporting
confidence: 91%
“…For example, 14/17 old females exhibited VHIPP IL-6 levels that exceeded the mean value measured in old males. These data are in line with other studies indicating that neuroinflammation accumulates in the aged female hippocampus to a greater extent than males [ 57 ] and highlights a potential mechanism whereby females display faster age-related cognitive decline than men [ 81 ] and higher rates of Alzheimer’s disease [ 82 ]. It will be of interest to future studies to understand the basis for these augmented female responses.…”
Section: Discussionsupporting
confidence: 91%
“…These factors lead to a higher vascular risk and could be directly related to higher dementia cases in women in the long run (Zhong et al, 2015). Lastly, the sex differences noted in dementia are not really prominent until after the age of 80, and that is only consistent in studies done in the United States (Podcasy and Epperson, 2016;Levine et al, 2021). Other studies in Europe show a sex difference in VaD early on, indicating that the occurrence of VaD can be influenced by external factors (Hasselgren et al, 2020).…”
Section: Sex-specific Differences In Vadmentioning
confidence: 96%
“…It is noteworthy that agerelated changes in cognition also differ by sex. For instance, a recent study has observed that while women had significantly higher baseline global memory, executive function, and memory performance than men, they showed significantly faster declines in the global memory and executive function (Levine et al, 2021). Another study found that older men had steeper rates of decline on measures of perceptuomotor speed and integration as well as visuospatial abilities (McCarrey et al, 2016).…”
Section: Introductionmentioning
confidence: 99%